Effect of Ultrasonic and Diode Laser Irrigation Activation on Post-operative Pain and Microbial Reduction in Single Visit Endodontic Treatment of Necrotic Mandibular Molars - Elmallawany, Ahmed; Hussein, Yasser F.; Ali, Magdy M.; Montasser , Karim; Aly, Yousra; Sharaf, Nehal (Open Access Macedonian Journal of Medical Sciences, 2022)
Aim: To clinically evaluate the effect of continuous ultrasonic and diode laser 810 wave length irrigation activation techniques on postoperative pain and bacterial reduction in single visit endodontic treatment of mandibular molars. Material and methods: Forty patients requiring root canal treatment therapy for necrotic mandibular molars teeth were included in this study with age ranges between 20 and 45 years. In all cases, single visit endodontic treatment was carried out using Revo-S rotary file system in crown down sequence. NaOCl 2.5% irrigation solution was used during treatment. Patients were randomly and equally assigned into two groups according to irrigation technique. Group (1): conventional syringe irrigation and group (2): continuous ultrasonic irrigation. Each group was subdivided into two sub groups (n = 10); subgroup 1A (conventional syringe irrigation with no laser), subgroup 1B (conventional syringe irrigation with diode laser), subgroup 2A (continuous ultrasonic irrigation with no laser) and subgroup 2B (continuous ultrasonic irrigation with diode laser). Postoperative pain evaluation was done using Visual Analogue Scale (VAS) at 6, 12, 24, 36, 48 hours and 7 days postoperatively. Microbiological detection of bacterial reduction was done by taking Samples (S1 and S2) for bacterial cultures. S1 after finishing access cavity and before mechanical preparation and S2 after finishing mechanical preparation and irrigation activation and before obturation. Samples were cultured on blood agar and determined as colony forming units (CFU/mL). Microbiological bacterial reduction was calculated accordingly. Statistical analyses were analyzed using the Mann-Whitney U test. The significance level was set at p < 0.05. Results: In all sub groups, postoperative pain decreased by time in all time intervals but pain was significantly lower in subgroup (2B) (continuous ultrasonic irrigation with diode laser) than subgroup (1A) (conventional syringe irrigation with no laser) in all time interval. Microbiological results showed the highest bacterial reduction was in subgroup (2B) (continuous ultrasonic irrigation with diode laser) and least bacterial reduction was in subgroup (1A) (conventional syringe irrigation with no laser). Conclusion: Using diode laser and continuous ultrasonic irrigation activation techniques as adjunctive methods showed improvement in postoperative pain records and enhanced bacterial reduction in root canal therapy. Keywords: Continuous ultrasonic irrigation, diode laser 810, post-operative pain, bacterial reduction, single visit endodontic treatment.